Jurnal Pengaruh Penggunaan Media Belajar Powtoon Terhadap Motivasi Belajar IPA di Kelas 5 Sekolah Dasar - Ratih (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to determine the effect of using powtoon learning media on the motivation to learn science in class 5 SDN Cengkareng Timur 05 Pagi. This research is a quantitative research using survey method. The population in this study were students of class 5 B totaling 35 students. The data collection technique in this study was using a questionnaire. Information obtained from respondents using this questionnaire is used to find the effect of using powtoon learning media on science learning motivation. This study uses a partial test (t test) to determine the hypothesis. The results of the hypothesis obtained based on partial testing (t test) are 3,910 (tcount) > 2,034 (ttable) with a significance of 0,000 < 0,005. These results indicate that H1 is accepted and Ho is rejected, which means that there is a positive and significant influence between the powtoon learning media on the science learning motivation of the fifth grade B SDN Cengkareng Timur 05 Pagi.